COLLABORATION PROBLEMS AND THEIR SOLUTIONS - Amanov, Alisher (Журнал иностранных языков и лингвистики, 2023)
Our article looks at problems in collaborative work and their possible solutions. The works and opinions of some scientists and researchers are analyzed and summarized.